(3JKbja GddSGfs - (3CHh MaU YeQ Hf Nda Hf ecj GdUbdj GdfMhjs
(3ChdgG (B:s
(3bGd GdTjN CHh MaU YeQ Hf eci GdUbdi GdfMhi GdMeO ddg GdPi aVdfG HGddSGf GdYQHi gLe GdaSGO Ydi GddSGf hNGdWJ GdGSGAI GdGMSGf hONdJ dZI GdYQH SCdfi hQZH Edi Gf GLeY dg eG JUMa GdfGS ai CdaGXge s
(3BNQgG (B:s
(3YeQ QVi Gddg Yfg GdfLGTi hbGd Ef YOJ UWYJ dSGfc hcGf YeQ QVi Gddg Yfg jYde ef GdTYQ eG jYde MSGf hdcfg GQGO GdMLI Hg QVi Gddg YfgeG Je GdcJGH hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B226s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GddZIs